Synthesis and characterization of a new asymmetrical phthalocyanine with Zn(II), Ni(II) and Co(II) - Canlica, Mevlude (ASIAN JOURNAL OF CHEMISTRY, 2008)
In present studies, the synthesis and characterization of a new asymmetrically substituted metallophthalocyanine has been reported. Statistical condensation of two different dinitrile derivatives has been applied to synthesize asymetrical metallophthalocyanine. In the first part of this study, 1,2-dichloro-4,5-dicyanobenzene and 1,2bis(hexylthio)-4,5-dicyanobenzene was obtained as two dinitrile derivative. In the second part of the study, this products were reacted in the presence of a metal salt. The newly synthesized phthalocyanines were seperated by column chromatography on silica gel and washed with common organic solvents. The structures of the synthesized compounds were characterized by the elemental analyzes, UV/Vis, FT-IR and H-1 NMR spectroscopies.
Keywords: asymetrical phthalocyanine; Zn(II); Ni(II); Co(II); metallophthalocyanine; Chemistry